2011
DOI: 10.1093/pcp/pcr053
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Cysteine-Rich 10 kDa Prolamin in Protein Body I Formation in Rice

Abstract: The rice prolamins consist of cysteine-rich 10 kDa (CysR10), 14 kDa (CysR14) and 16 kDa (CysR16) molecular species and a cysteine-poor 13 kDa (CysP13) polypeptide. These storage proteins form protein bodies (PBs) composed of single spherical intracisternal inclusions assembled within the lumen of the rough endoplasmic reticulum. Immunofluorescence and immunoelectron microscopy demonstrated that CysR10 and CysP13 were asymmetrically distributed within the PBs, with the former concentrated at the electron-dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 40 publications
0
53
0
3
Order By: Relevance
“…In this study, however, globulin-less mutation was unique to induce partial degradation of glutelin rather than compensation. Although compositional change of protein bodies induced by RNAi was demonstrated to result in irregular structure of PB in maize (Holding, 2014), wheat (Gil-Humanes et al, 2011), and rice (Kawakatsu et al, 2010;Nagamine et al, 2011), partial degradation has not ever been reported. Considering our results together with the fact that globulin accumulates on the surface of PB-II (Krishnan et al, 1992;Kumamaru et al, 2010) and its absence results in structurally deformed PB-II (Ashida et al, 2011), globulin protects glutelins from proteinase digestion and thereby facilitates stable glutelin accumulation.…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 97%
“…In this study, however, globulin-less mutation was unique to induce partial degradation of glutelin rather than compensation. Although compositional change of protein bodies induced by RNAi was demonstrated to result in irregular structure of PB in maize (Holding, 2014), wheat (Gil-Humanes et al, 2011), and rice (Kawakatsu et al, 2010;Nagamine et al, 2011), partial degradation has not ever been reported. Considering our results together with the fact that globulin accumulates on the surface of PB-II (Krishnan et al, 1992;Kumamaru et al, 2010) and its absence results in structurally deformed PB-II (Ashida et al, 2011), globulin protects glutelins from proteinase digestion and thereby facilitates stable glutelin accumulation.…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 97%
“…However, plants differ from animals in that they also produce different types of ER-derived vesicles, and these are involved in the accumulation of proteins (Galili, 2004;Hara-Nishimura et al, 2004;Herman and Schmidt, 2004;Herman, 2008). Protein bodies (PBs) store seed storage proteins in the endosperm of maize (Zea mays) and rice (Oryza sativa; Herman and Larkins, 1999;Satoh-Cruz et al, 2010;Nagamine et al, 2011). Precursoraccumulating vesicles accumulate seed protein precursors in the maturing cotyledons of pumpkin (Cucurbita maxima; Hara-Nishimura et al, 1998).…”
mentioning
confidence: 99%
“…The hydropathy plots of 13a prolamin suggest that the M and C domains are more hydrophobic than the N domain. 24) Therefore, 13a prolamin could aggregate in the ER via the hydrophobicity of the M and/or C domain.…”
Section: Discussionmentioning
confidence: 99%